Simultaneous Determination of Methotrexate, Dasatinib and its Active Metabolite N- Deshydroxyethyl Dasatinib in Rat Plasma by LC-MS/MS: Method Validation and Application to Pharmacokinetic Study - Thappali, S.R. S.; Varanasi, K.V. S.; Veeraraghavan, S.; Vakkalanka, S.K.V. S.; Khagga, M. (Arzneimittelforschung, 2012)
Dasatinib is a multi-kinase inhibitor that potently inhibits Bcr-Abl, Src family and platelet-derived growth factor receptor kinases. Methotrexate is an antimetabolite and antifolate drug. Clinical trials utilizing a combination of dasatinib and methotrexate in patients with Philadelphia chromosome positive and/or Bcr-Abl positive acute lymphoblastic leukemia are currently ongoing. A need therefore exists to develop a sensitive analytical method for determination of dasatinib and methotrexate in plasma.To estimate methotrexate, dasatinib and its active metabolite N-deshydroxyethyl dasatinib simultaneously using liquid chromatography-electrospray ionization tandem mass spectrometry (HPLC-ESI-MS/MS) in Wistar rat plasma.The analytes were extracted by using liquid-liquid extraction procedure and separated on a reverse phase C18 column (50 mm×3 mm i.d., 4.6 µ) using methanol: 2 mM ammonium acetate buffer, pH 4.0 as mobile phase at a flow rate 1 mL/min in gradient mode. Selective reaction monitoring was performed using the transitions m/z 455.0>175.0, 488.1 > 401.0, 444.26>401.0, and 271.1>− 155.0 to quantify methotrexate, dasatinib, N-deshydroxyethyl dasatinib and tolbutamide respectively.The method was validated over the concentration range of 1–1 000 ng/mL and the lower limit of quantitation was 1 ng/mL. The recoveries from spiked control samples were > 79% for all analytes and internal standard Intra- and Interday accuracy and precision of validated method were within the acceptable limits of < 15% at all concentration.The quantitation method was successfully applied for simultaneous estimation of methotrexate, dasatinib and N- deshydroxyethyl dasatinib in a pharmacokinetic study in Wistar rats.
Keywords: methotrexate; dasatinib; N- deshydroxyethyl dasatinib; pharmacokinetics; LC-MS/MS